Aplicação do sensor leap motion como instrumento didático no ensino de crianças surdas - Felippsen, Eduardo Alberto (2017)
The technologies are in broad development and increasingly present in the students' daily life, a reality that can be appropriated by the school for the creation of new teaching strategies. In the case of teaching deaf children, the use of technologies may be even more effective, since the visual aspect should be privileged. In this context, this dissertation presents, by means of a qualitative research with action-research methodology, the application of the Leap Motion Gesture Interaction Interface in classes for deaf children. The planning and selection of the softwares took place together, involving the researcher and the teachers of the Training Center of the Professionals of the Education and Assistance to Persons with Deafness (in Portuguese, Centro de Capacitação dos Profissionais da Educação e Atendimento às Pessoas com Surdez) in the city of Cascavel / PR, this, in the generation of lesson plans. It was identified that the communication and mediation of the teacher are key-factors for the student to interpret and understand the interaction environment, as well as the task that is expected to be realized. This, because the student is in training in the Brazilian Sign Language (in Portuguese, Língua Brasileira de Sinais - Libras) and hasn’t knowledge of the written Portuguese language. In other words, there is a strong dependence of the teacher to that him/her interprets the interface of the software and translates it to Libras, inserting in this translation elements that result in the understanding by the child. As results, it was verified that, in well-planned use scenarios, there was the contribution of the use of the Leap Motion sensor in the learning, and that there was a significant contribution in the social interaction and the collaboration between the students in the accomplishment of the tasks. These aspects of interaction among students can be also considered in the elaboration of new teaching strategies supported by gestural interfaces.